A comparative study of three-dimensional airway changes after fibula flap reconstruction for benign and malignant tumours in the anterior mandible. Issue 6 (June 2023) - Du, W.; Liu, G.; Zhang, W.; Zhao, N.; Shi, Y.; Peng, X.
Abstract: Surgical treatment of tumours in the anterior mandible and surrounding tissues may result in defects which can be restored by a fibula free flap. The upper airway may change during this process. The purpose of this retrospective study was to evaluate upper airway changes after fibula free flap reconstruction. A total of 37 patients who underwent anterior mandibulectomy and fibula free flap reconstruction between 2012 and 2020 were recruited. Patients with benign and malignant tumours involving the anterior mandible were included. Spiral computed tomography was performed 1 week preoperatively, 1 week postoperatively, and at> 1 year (range 12–23 months) after surgery. Cross-sectional areas and volumes of the upper airway were measured. Data were analysed by two-way analysis of variance. The upper airway in the malignant tumour group showed an increasing trend, especially at the soft palate and tongue base levels ( P  < 0.01). In the benign tumour group, the upper airway showed no significant changes. The location of the minimum cross-sectional area moved downwards in both groups, and the area increased in the malignant tumour group during long-term follow-up. Upper airway obstruction is less likely to occur in the long term after surgical resection of anterior mandible malignancies and fibula free flap reconstruction.